Gradual cerebral hypoperfusion in spontaneously hypertensive rats induces slowly evolving white matter abnormalities and impairs working memory. Issue 9 (September 2016) - Kitamura, Akihiro; Saito, Satoshi; Maki, Takakuni; Oishi, Naoya; Ayaki, Takashi; Hattori, Yorito; Yamamoto, Yumi; Urushitani, Makoto; Kalaria, Raj N; Fukuyama, Hidenao; Horsburgh, Karen; Takahashi, Ryosuke; et al.
Rats subjected to bilateral common carotid arteries (CCAs) occlusion or 2-vessel occlusion (2VO) have been used as animal models of subcortical ischemic vascular dementia (SIVD). However, these models possess an inherent limitation in that cerebral blood flow (CBF) drops sharply and substantially after ligation of CCAs without vascular risk factors and causative small vessel changes. We previously reported a novel rat model of 2-vessel gradual occlusion (2VGO) in which ameroid constrictors (ACs) were placed bilaterally in the CCAs of Wistar-Kyoto rats. To simulate SIVD pathology more closely, we applied ACs in spontaneously hypertensive rats (SHRs), which naturally develop small vessel pathology, and compared their phenotypes with SHR-2VO and sham-operated rats. The mortality rate of the SHR-2VGO was 0% while that of the SHR-2VO was 56.5%. The CBF of the SHR-2VO dropped to 50% of the baseline level at 3 h, whereas the SHR-2VGO showed a gradual CBF reduction reaching only 68% of the baseline level at seven days. The SHR-2VGO showed slowly evolving white matter abnormalities and subsequent spatial working memory impairments of a similar magnitude to the remaining SHR-2VO at 28 days. We suggest the SHR-2VGO robustly replicates selective aspects of the pathophysiology of SIVD with low mortality rate.